John Armor Bingham papers - Bingham, John Armor, 1815-1900.
Correspondence, speeches, writings, biographical sketch, certificates, and printed material pertaining chiefly to Bingham's service as a Republican U. S. representative from Ohio (1855-1863, 1865-1873) and as U. S. minister to Japan (1873-1885). Subjects include Abraham Lincoln, the impeachment of Andrew Johnson, assassination of James A. Garfield, the Kansas-Nebraska Act, and the war with Mexico.
Lawyer, jurist, diplomat, U.S. House representative, and co-author of the 14th amendment to the U.S. Constitution.
Collection material in English.
Keywords: Garfield, James A. -- 1831-1881 -- Assassination; Lincoln, Abraham, -- 1809-1865.; Johnson, Andrew, -- 1808-1875 -- Impeachment; Diplomatic and consular service, American; Impeachments -- United States; Mexican War, 1846-1848.; Slavery -- United States; Trials (Impeachment) -- United States; United States; Japan -- Foreign relations -- United States; Kansas -- Politics and government; Mexico -- Foreign relations -- United States; Nebraska -- Politics and government; United States -- Foreign relations -- 19th century; United States -- Foreign relations -- Japan; United States -- Foreign relations -- Mexico; United States -- Politics and government -- 19th century; Diplomats; Jurists; Representatives, U.S. Congress -- Ohio